Profiling gene expression pattern changes in HIV-1-associated kidney disease - Mpye, Keleabetswe Lerato (My University, 2016)
HIV-1 infected individuals are at risk of developing clinically and morphologically diverse renal complications. Most of the ensuing renal complications are similar to those observed in non-HIV patients while some are limited to HIV-infected patients. Kidney diseases are amongst the top 10 leading causes of death in the general population and affect over 10 % of the adult population. Two to ten percent of HIV-1 infected patients ultimately suffer chronic kidney disease, and specifically HIV-associated nephropathy (HIVAN), characterized clinically by nephrotic range proteinuria and histologically by collapsing focal segmental glomerulosclerosis (FSGS). Genetic mutations and disruption of the podocyte foot process and actin-based cytoskeleton architecture through dysregulation of its principal element, actin, or its associated proteins, lead to proteinuria and nephrotic syndrome. The majority of these proteins are susceptible to proteolysis by a lysosomal cysteine protease, cathepsin-L. The current study set out to profile changes in gene expression in HIVAN relative to HIV negative FSGS, minimal change disease (MCD) and non-proteinuric healthy controls. Probing the presence and localization of cathepsin-L and dynamin in these proteinuric kidney diseases, we showed that cathepsin-L and dynamin expression is enhanced in HIVAN and FSGS, relative to the healthy controls and MCD. We further profiled the expression of the 3 isoforms of cathepsin-L and dynamin using Quantitative reverse transcriptase PCR. CTSL-3 expression was similar between all disease groups whilst CSTL-2 was reduced relative to the normal tissue. There was most variation in the expression of CSTL- 1 between the disease tissues with down-regulation of CSTL-1 in both HIVAN and FSGS relative to the control and MCD tissue. The expression of dynamin remained largely unchanged between the disease groups with the exception of DYN-1 which was downregulated in MCD relative to FSGS. Given that dynamin expression was barely altered across the proteinuric states, compared to the healthy non-proteinuric controls, signifies that proteolysis of the actin-associated proteins synaptopodin and/or slit diaphragm-associated CD2AP by the cathepsins-L 2 and 3 was responsible for the proteinuria in HIVAN, FSGS and MCD. Our results show that FSGS manifests through attenuated CD2AP, up-regulated TGF-β1 and cathepsin-L activity and not via dynamin degradation. The attenuated mRNA expression levels of dynamin, CD2AP and synaptopodin in renal tissue of the proteinuric kidneys validate that podocyte injury, in the form of loss of foot process integrity and slit diaphragm permeability, manifests through the over-expressed cathepsin-L enzymatic activity. Many of the genes that were altered in proteinuric kidney diseases, as observed from the pathway analysis of the PCR array data, are mediated by transcriptional activation of nuclear factor kappa B (NF-ΚB). Transcriptional mRNA expression levels, validated in real-time quantitative RT-PCR analysis illustrated that HIV-1 infection induces uncontrolled activation and induction of immunity and inflammatory responses, indicated by down-regulation of SIGIRR, and modulation of expression patterns of immunity and inflammatory response genes in proteinuric kidney diseases. Other genes that were down-regulated in HIVAN are involved in the MAPK JNK cellular signaling pathway and apoptosis. HIV-1 infection modulates expression patterns of the genes that are involved in immunity and inflammatory responses in proteinuric kidney disease, compromising the structure and function not only of the kidney but of the entire immune system.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2015